Atalhos informacionais, sofisticação política e a escolha do voto em diferentes contextos políticos: as eleições presidenciais de 2002 no Brasil - Vinícius Campos Freitas (2012)
The purpose of this study is to assess the importance of different types of informational shortcuts had in structuring electoral choices in the 2002 presidential elections. Shortcuts works as summary information of more complex political events that decrease the costs involved in acquiring and processing information, allowing for consistent and rational assessment of political situation even under low-information. This study uses data from a survey in panel format used throughout the year 2002 in Juiz de Fora and Caxias do Sul, two cities with similar socioeconomic characteristics, but with different political environments. The hypothesis is that crafted the strategies in the voting decision are different depending on the available cognitive resources, the environment and the time of the election campaign. Therefore, it was expected that those with higher levels of political sophistication would be more likely to be guided by ideological or partisan issues that require greater cognitive effort. Since individuals with lower levels of political knowledge are more likely to use shortcuts that relate to the image, the attributes that denote political competence or endorsement of candidates provided by groups or other political leaders. Besides the political context of cities, the moment electoral campaigns and decreasing the task of having to decide the vote. The results confirm, in parts, such expectations. Over time, the partisan and ideological shortcuts remain important in the choice of the voter, without as many restrictions as to the degree of cognitive sophistication, as shortcuts as evaluating the economic situation, endorsement and imaging become more significant, although the significance statistics is tied to variable political sophistication.